Visual Perception Strategies during Anticipation of the Kuda and the Sila Service in Sepak Takraw - Abdullah, Mohamad Razali (2007)
Two major types of services in sepak takraw are kuda and sila services. Even though both services are delivered at high speed, each is composed of different kinematic features. As a result, the receiver in the game is constantly playing under severe time constraint in his effort to intercept the service action from the opponent. The purpose of the study was to determine the fundamental differences in perceptual strategies in anticipating the kuda and sila services. It was hypothesized that players would employ different perceptual strategies to overcome the time constraint. The receiver of the game in sepak takraw makes decisions under severe time constraint in both spatial and temporal uncertainty. Previous research showed that success in the game depended on visual perception of the players as well as the efficiency and accuracy of the interceptive actions. There were also evidence of players using advance visual kinematic cues to guide their anticipatory responses. The ability to use kinematic cues is extremely crucial in ballistic sports where speed of the game and velocity of the ball dictate the decision which must often be made ahead of time. Thus, this study was conducted on the premise that anticipation depends upon kinematic information. In turn, kinematic information induces varying anticipatory demands. To test the research hypotheses, the study was conducted in two phases; (i) temporal analyses of the kuda and sila services and (ii) visual perceptual strategies in anticipating the kuda and sila services. Kinematic data for the first phase of the study was obtained from a video recording of a sepak takraw match during the Kuala Lumpur Sea Games 2001. Peak Motus 7.0 software was used to perform a three dimensional temporal analysis on 50 randomly selected services of each type. The main focus of the first phase of the study was to conduct temporal analyses on the movements for each type of services based on pre determined temporal phases. The second phase of the study examined two groups of 12 players each; the experts and the novices. Players’/ The visual perceptual displays in anticipation of the kuda and sila services were prompted using video stimulations consisting of 7 temporal occlusions t1 (240 milliseconds at pre-contact), t2 (160 milliseconds at pre-contact), t3 (80 milliseconds at pre-contact, t4 (0 millisecond at contact), t5 (80 milliseconds at post-contact), t6 (160 milliseconds at post-contact), and t7 (no occlusion). The findings of the study revealed that there were significant differences in the temporal features of kuda and sila services during the pre-contact [F(1,99) = 3421.25; p< .05], contact [F(1,99) = 31.96; p< .05], post-contact [F(1,99) = 91.93; p< .05], and movement time of the receiver [F(1,99) = 409.39; p< .05]. Confidence interval analyses showed significant differences among experts in anticipating kuda service at t1. Significant differences amongst expert players in anticipating kuda and sila services were at t1 [F(14,180) = 2.37; p< .05], t2 [F(14,180) = 5.60; p< .05], t3 [F(14,180) = 3.81; p< .05] dan t4 [F(14,180) = 2.00; p< .05]. Similar comparisons at t5, t6, and t7 did not yield any significant differences. In addition, there were significant differences amongst novice players in anticipating kuda and sila services at t2 t2 [F(14,180) = 2.27; p< .05], t3 [F(14,180) = 1.94; p< .05], t4 [F(14,180) = 2.61; p< .05], and t5 [F(14,180) = 9.38; p< .05]. However, significant differences were not observed at t1, t6, and t7 amongst these same players. Two hypothetical models have been established from the study of temporal analyses, namely Hypothetical Model of the Kuda Service and Hypothetical Model of the Sila Service. The study showed that expert players found it harder to anticipate kuda service compared to sila service at t1. Hence, the kuda service is more difficult to anticipate than sila service. The participants of this study demonstrated a more effective/ efficient visual perceptual strategy to counterattack a sila service than they would a kuda service. Finally, it is proposed that a combination of spatial occlusion and point light display be utilized to identify the types of information that players should focus on as anticipatory cues. Future study should look into the combination of both motor and perceptual skills in facilitating better decision making by players. In addition, further exploration using semi-longitudinal study, 3D image technique, and varying time frames is strongly recommended.